Fiction in the quantum universe - Strehle, Susan (University of North Carolina Press, 1992)
Susan Strehle argues that a new fiction has developed from the influence of modern physics. The changed physical world appears in both content and form in some of the most ambitious recent fiction, which Strehle names "actualism" after the observations of Werner Heisenberg. Within that framework she explores the meditations on actuality in Pynchon, Coover, Gaddis, Barth, Atwood, and Barthelme. Although important recent narratives diverge markedly from realistic practice, this book claims that they do so in order to reflect more acutely on what we now understand as real. According to Strehle, the actualists balance attention to questions of art with an engaged meditation on the external, actual world. Reality is no longer realistic; in the new physical or quantum universe, it is discontinuous, energetic, relative, statistical, subjectively seen, and uncertainly known--all terms taken from the new physics. Actualist fiction is characterized by incompletions, indeterminacy, and "open" endings unsatisfying to the readerly wish for fulfilled promises and completed patterns. Gravity's Rainbow, for example, ends not with a period but with a dash. Realistic novels typically construct solid, believable, particularized environments, but actualist texts combine the plausible and the strange. Thus a recognizable campus like Berkeley or Cornell has a suburb called San Narciso or Zembla. Strehle makes the point that these innovations in narrative form reflect in allied ways upon twentieth-century history, politics, and science. Arguing that the perception of a changed reality reaches into philosophy, psychology, literary theory, and other areas of inquiry, the book advances a pluralistic view of the meaning of contemporary fiction. A final chapter extends the discussion beyond the North American borders to African, South American, and European texts, suggesting a global community of writers whose fiction belongs in the quantum universe